Oxidation behavior of liquid-phase sintered silicon carbide with aluminum nitride and rare-earth oxides (Re2O3 where Re=Y, Er, Yb) - Choi, HJ; Lee, JG; Kim, YW (AMER CERAMIC SOC, 2002)
Silicon carbide (SiC) ceramics have been fabricated by hot-pressing and subsequent annealing under pressure with aluminum nitride (AIN) and rare-earth oxides (Y2O3, Er,031 and Yb2O3) as sintering additives. The oxidation behavior of the SiC ceramics in air was characterized and compared with that of the SiC ceramics with yttrium-aluminum-garnet (YAG) and Al2O3-Y2O3-CaO (AYC). All SiC ceramics investigated herein showed a parabolic weight gain with oxidation time at 1400degreesC. The SiC ceramics sintered with AIN and rare-earth oxides showed superior oxidation resistance to those with YAG and Al2O3-Y2O3-CaO. SiC ceramics with AIN and Yb2O3 showed the best oxidation resistance of 0.4748 mg/cm(2) after oxidation at 1400degreesC for 192 h. The minimization of aluminum in the sintering additives was postulated as the prime factor contributing to the superior oxidation resistance of the resulting ceramics. A small cationic radius of rare-earth oxides, dissolution of nitrogen to the intergranular glassy film, and formation of disilicate crystalline phase as an oxidation product could also contribute to the superior oxidation resistance.
Keywords: MECHANICAL-PROPERTIES; CERAMICS; STRENGTH; GLASSES; SI3N4; MICROSTRUCTURE; ADDITIONS; SYSTEM